Back Cover: Assessment of the dynamics of human glymphatic system by near‐infrared spectroscopy (J. Biophotonics 8/2018). Issue 8 (8th August 2018) - Myllylä, Teemu; Harju, Markus; Korhonen, Vesa; Bykov, Alexander; Kiviniemi, Vesa; Meglinski, Igor
Abstract : A functional near‐infrared spectroscopy (fNIRS) based approach to non‐invasive monitoring of the (g)lymphatic system in the human brain. The cover figure shows depth sensitivity of fNIRS, particularly at the wavelength of 980 nm, for sensing dynamic variations of water and cerebrospinal fluid (CSF) volume, e.g. in the subarachnoid space. Observed fluctuations in water content correlated with magnetic resonance encephalography (MREG) signals during visual task, further, are assumed to be connected with the glymphatic circulation. Further details can be found in the article by Teemu Myllylä, Markus Harju, Vesa Korhonen, et al. (e201870154 ) Abstract : A functional near‐infrared spectroscopy (fNIRS) based approach to non‐invasive monitoring of the (g)lymphatic system in the human brain. The cover figure shows depth sensitivity of fNIRS, particularly at the wavelength of 980 nm, for sensing dynamic variations of water and cerebrospinal fluid (CSF) volume, e.g. in the subarachnoid space. Observed fluctuations in water content correlated with magnetic resonance encephalography (MREG) signals during visual task, further, are assumed to be connected with the glymphatic circulation. Further details can be found in the article by Teemu Myllylä, Markus Harju, Vesa Korhonen, et al. (e201870154 )